2019
DOI: 10.1007/s41999-019-00213-0
|View full text |Cite
|
Sign up to set email alerts
|

Severity of both neuropsychiatric symptoms and dementia is associated with quality of life in nursing home residents

Abstract: The aim was to investigate the association of severity of neuropsychiatric symptoms and health-related quality of life and their interaction with dementia severity among institutionalized older people with dementia. Findings Neuropsychiatric symptom burden was associated with higher health-related quality of life in residents with severe dementia, whereas among those residents with mild-moderate dementia this association was not seen. Very low functional capacity was linked to both low number of neuropsychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
2
3
1
2
Order By: Relevance
“…In particular, agitation, aggression, irritability, disinhibition, euphoria and apathy scores were higher in those with increased dementia severity. Similar findings have been reported in previous studies examining people with different types of dementia (AD, VaD and FTD) in community 6,7 and RAC contexts 8,9 . Findings from our study also showed that dementia severity was negatively associated with the quality of life.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In particular, agitation, aggression, irritability, disinhibition, euphoria and apathy scores were higher in those with increased dementia severity. Similar findings have been reported in previous studies examining people with different types of dementia (AD, VaD and FTD) in community 6,7 and RAC contexts 8,9 . Findings from our study also showed that dementia severity was negatively associated with the quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…8 A more recent cross-sectional cohort study in RAC facilities in Helsinki showed that the severity of neuropsychiatric symptoms and dementia severity were significant factors determining health-related quality of life. 9 In this study, higher scores in neuropsychiatric symptoms were associated with better quality of life in residents with severe dementia, while this association was not observed for mild-to-moderate dementia. The authors suggested that the differences may be partly due to study population, due to the inclusion of a higher proportion of residents with severe dementia (67%) in their which can be used to inform targeted, person-centred dementia care planning, staff training and allocation of resources.…”
Section: Introductioncontrasting
confidence: 49%
See 2 more Smart Citations
“…It shows good correlation with other well‐established symptom rating scales. A total NPI score of >3 indicates clinically relevant symptoms, 4–12 indicates low symptom burden and ≥12 indicates high symptom burden 23 . Maximum total score is 144.…”
Section: Methodsmentioning
confidence: 99%